Financial Inclusion and Monetary Policy - Investigating the Relationship between Financial Inclusion and Monetary Policy: The Case of Egypt - Maher, Salma (AUC Knowledge Fountain, 2022)
In the past decade, financial inclusion has become an issue of increasing importance to developing nations. This is due to its perceived effects on poverty alleviation, sustainable growth and enhancing monetary policy effectiveness. Unfortunately, there is little empirical research on the effects of financial inclusion. The thesis hopes to contribute to the literature by inspecting the relationship between financial utilization indices and monetary policy in Egypt. The thesis utilizes quarterly data on outstanding deposits and loans from 2004 to 2020 as well as a VAR model – supplemented with an ARDL model – to test the aforementioned relationship. The thesis contributes to the literature by inspecting which of the following sectors – households or SMEs – are more conducive to monetary policy efficiency in order to develop more tailored policy recommendation. The findings imply a significant and negative relationship between total deposits by both households and SMEs to inflation. Some specifications imply the existence of a significant positive relationship between loans authorized to SMEs and inflation, implying an instance of over indebtedness in the sector that can impact the overall financial stability